Hamstring rehabilitation in elite track and field athletes: applying the British Athletics Muscle Injury Classification in clinical practice. Issue 23 (12th July 2019) - Macdonald, Ben; McAleer, Stephen; Kelly, Shane; Chakraverty, Robin; Johnston, Michael; Pollock, Noel
Abstract : Rationale: Hamstring injuries are common in elite sports. Muscle injury classification systems aim to provide a framework for diagnosis. The British Athletics Muscle Injury Classification (BAMIC) describes an MRI classification system with clearly defined, anatomically focused classes based on the site of injury: (a) myofascial, (b) muscle–tendon junction or (c) intratendinous; and the extent of the injury, graded from 0 to 4. However, there are no clinical guidelines that link the specific diagnosis (as above) with a focused rehabilitation plan. Objective: We present an overview of the general principles of, and rationale for, exercise-based hamstring injury rehabilitation in British Athletics. We describe how British Athletics clinicians use the BAMIC to help manage elite track and field athletes with hamstring injury. Within each class of injury, we discuss four topics: clinical presentation, healing physiology, how we prescribe and progress rehabilitation and how we make the shared decision to return to full training. We recommend a structured and targeted diagnostic and rehabilitation approach to improve outcomes after hamstring injury.